Return to Play in Adolescent Baseball Players after SLAP Repair (131). Issue 10 (31st October 2021) - Rao, Somnath; Jeyamohan, Hareindra; D'Amore, Taylor; Jack, Robert; Acharya, Pankti; Cohen, Steven; Dodson, Christopher; Ciccotti, Michael
Objectives: Superior labrum from anterior to posterior (SLAP) tears are increasingly common shoulder injuries in adolescent athletes who participate in repetitive overhead throwing. The purpose of this study is to evaluate adolescent baseball athletes who undergo SLAP repair in order to determine their long-term progression of play, surgical outcomes, and overall satisfaction with surgery. Methods: Patients between the ages of 10-19 who underwent a SLAP repair over a 10-year period from 2008-2018 with minimum two year follow-up were identified by a database query in the medical records of a single institution. From this cohort, non-baseball athletes and injuries to non-throwing shoulders were excluded. After identifying the cohort, patients were contacted via phone to complete functional outcome scores including Conway Score, Western Ontario Shoulder Instability (WOSI) Index, Kerlan-Jobe Orthopedic Clinic (KJOC) Shoulder and Elbow Score, Short Form 12 Mental (MCS)/Physical (PCS) survey and a custom return to play questionnaire. Results: During this time period, 59 baseball players met the inclusion criteria for this study and 76.3% (45/59) of patients were available to be contacted to complete final follow-up surveys at a minimum of 2 years. All patients were male with a mean age of 17.4 +/- 1.5 (14-19) years. The mean follow-up of this cohort was 5.3 +/- 2.6 (2.1-12.1) years. The overall return to play rate was 75.6% (34/45). The average time from surgery to initiation of throwing was 5.9 +/- 2.0 (2-12) months and the average time to return to full competition was 11.3 +/- 3.5 (6-22) months after the surgery. After the SLAP repair, those who returned to play continuing playing baseball competitively for 3.0 +/- 1.9 (0.5-8.0) years after surgery. At the time of final follow-up, 71.1% (32/45) of players had stopped playing baseball. Of those who had stopped playing competitive baseball, 12 (37.5%) reported it was because they were not recruited to the next level, 10 (31.3%) reported they lost the desire to play and 10 (31.3%) reported their shoulder prevented them from playing. The overall mean KOJC, WOSI, SF-12 MCS and SF-12 PCS scores were 60.0 +/- 27.4 (range, 0-100), 21.0+/-20.6% (0-73.8%), 55.2+/-3.9 (37.4-59.8) and 55.2+/-5.6 (range, 37.9-65.7) respectively. The overall satisfaction score was 83.2% with 86.7% (39/45) saying they given the opportunity they would undergo surgery again. Conclusions: The results of this study demonstrated a low return to play rate and low patient reported outcomes on baseball specific surveys among adolescent baseball players who underwent a SLAP repair. Mean functional outcome scores between pitchers and position players were not found to be significantly different. Based on these findings, orthopedic surgeons can better counsel their adolescent baseball players on expectations for future return to play and functional outcomes after SLAP repair.